Regulatory peculiar features of uncontrolled bronchial asthma - Romanchuk, O. P.; Bazhora, Ya. I. (Journal of Education, Health and Sport, 2018)
Bronchial asthma (BA) is a multifactorial disease which develops under the influence environmental factors in the presence of individual’s genetic predisposition. The mechanisms associated with the respiratory system dominate in its pathogenesis. The objective: to determine the regulatory features of the uncontrolled course of asthma. The results obtained. At the outpatient stage of treatment 71 male and female patients, mean age 41.0 ± 0.8 have been examined with the use of spiroarteriocardiorhythmography (SACRG). The patients under examination were divided into 2 groups: the group of comparison (n = 20), and the main one (n = 51). Alfa - coefficient in high (BRHF) and low (BRLF) frequencies, hemodynamic and minute volume of blood circulation (HMV, l), indexes of cardiovascular and respiratory systems synchronization and parameters of the cardiovascular system in patients with asthma were determined. Conclusions. In BA at the background of total respiratory capacity significant increase and growth of neurohumoral regulatory influences there is a significant decrease of the sympathetic link activity in the regulation of uncontrolled respiration and relative reduction of the volume velocity of inspiration, which should be taken into account when determining the severity of asthma.